Social responsibility: the involvement of entrepreneurs and organisations - Arsad, Jahjaiton; Awang, Rohana (2009)
The importance and benefits of social responsibility are increasingly significant among the people around the world. The level of involvement and contribution by people has improved from time to time. Social responsibility does not only attract the kind and warm-hearted entrepreneurs to be involved but also organisations (profit or non-profit), academicians, volunteers as well as politicians. This paper focuses on the approaches of social responsibility, the involvement of entrepreneurs and organisations, and the importance of social responsibility from the Islamic perspective. In addition, this paper also focuses on the background of well-known entrepreneurs around the world and their contributions. Lastly, in order to encourage the awareness of social responsibility, a few recommendations are proposed.